Fragmented Coronoid Process Associated with Premature Distal Radial Physeal Closure in Four Dogs - Macpherson, G. C.; Lewis, D.D.; Johnson, K.A.; Allen, G.S.; Yovich, Jane C. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Fragmented coronoid process occurred in four dogs with humeroradial subluxation secondary to premature closure of the distal radial physis. The medial coronoid process was affected in three dogs but in the fourth dog a single osteochondral fragment was located between the medial and lateral coronoid processes. One dog was treated by medial arthrotomy and lengthening of the radius. In three dogs the fragment was removed via a lateral arthrotomy accomplished by proximal ulnar diaphyseal osteotomy and the ulna was shortened at the ulnar osteotomy site to provide congruity of the proximal radio-ulnar and humeroradial articulations. The longterm clinical results were encouraging. The role of mechanical loading on the coronoid process in the pathogenesis of these cases is discussed.Four mature dogs were found to have fragmented coronoid process and humeroradial subluxation secondary to premature closure of the distal radial physis.It is proposed that the humero-radial subluxation placed ab-normal mechanical stress on the coronoid process of the ulna and caused its fracture or fragmentation.
Keywords: Fragmented coronoid process; humeroradial subluxation; elbow incongruity; physis; ulnar ostectomy